Building research capacity in a practitioner community: framing and evaluating the 'National Action Research Network on Researching and Evaluating Personal Development Planning and e-Portfolio Practice' - John Peters (Association for Learning Development in Higher Education (ALDinHE), 2010)
This paper evaluates key aspects of the National Action Research Network on Researching and Evaluating Personal Development Planning and e-Portfolio Practice (NARN). This was a National Teaching Fellowship Scheme funded project which ran from 2007-1010 and involved sixteen English Higher Education institutions (HEIs). The context, purposes, theoretical underpinnings and framework for the NARN are briefly explained before the experience of members is explored through an analysis of their own accounts. The NARN was proposed in response to widespread calls for more research evidence to underpin our understanding and implementation of Personal Development Planning (PDP) and e-Portfolio practices, taking its lead from Clegg's (2004) invitation to produce more researched examples of situated PDP and e-Portfolio practice. The NARN was primarily a capacity-building project aimed at developing a community of PDP and e-portfolio practitioners into practitioner researchers. Borrowing heavily on ideas of community and participative inquiry as well as concepts about developing communities of practice, the project placed an emphasis on promoting collegiality, a sense of belonging and the establishment of the project as a safe space in which to discuss research work. It is evaluated here through the thematic analysis of a particular data set of twelve anonymous accounts provided by project members. The NARN project's emphasis on process rather than product or output, mark it apart from most Higher Education (HE) learning and teaching funded projects. Its success carries an important lesson for fundholders, educational developers and HE managers about the funding of more process-based learning and teaching development in HE. It also provides a possible framework for similar capacity-building projects across other communities.